2019
DOI: 10.1109/jbhi.2018.2872834
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic and Kinetic Validation of an Improved Depth Camera Motion Assessment System Using Rigid Bodies

Abstract: The study of joint kinematics and dynamics has broad clinical applications including the identification of pathological motions or compensation strategies and the analysis of dynamic stability. High-end motion capture systems, however, are expensive and require dedicated camera spaces with lengthy setup and data processing commitments. Depth cameras, such as the Microsoft Kinect, provide an inexpensive, marker-free alternative at the sacrifice of joint-position accuracy. In this work, we present a fast framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 44 publications
0
27
1
Order By: Relevance
“…Finding an unobtrusive and easy-to-use solution is quite difficult. Camera-based detection systems, which include marker-based and markerless human motion capture technologies [13], [14]. Marker-based motion tracking systems can achieve accurate and robust results, This work is licensed under a Creative Commons Attribution 4.0 License.…”
Section: A Compensation Detectionmentioning
confidence: 99%
“…Finding an unobtrusive and easy-to-use solution is quite difficult. Camera-based detection systems, which include marker-based and markerless human motion capture technologies [13], [14]. Marker-based motion tracking systems can achieve accurate and robust results, This work is licensed under a Creative Commons Attribution 4.0 License.…”
Section: A Compensation Detectionmentioning
confidence: 99%
“…This paper introduces a fast method for performing fullbody contactless dynamic analysis of the STS action using a single depth camera. Building on the author's prior results in improving the accuracy of the Kinect for STS actions by imposing rigid-body constraints [45], this work adds reducedcomplexity allometrically-scaled dynamic and musculoskeletal models. This provides estimates of torso momenta and joint torques of the low back, and lower limbs, key metrics that have been shown to act as correlates of disability in patient populations.…”
Section: B Contributionsmentioning
confidence: 99%
“…This method was chosen for the fast computation rate (524 fps) and the availability of commercial depth camera systems which can estimate the location of joint centres from a RGB-Depth image. The full kinematic recovery process is presented in the associated kinematic validation paper [45]. A brief overview is given below for completeness.…”
Section: A Prior Data: Kinematicsmentioning
confidence: 99%
“…Most similar studies typically reported the validity of using the proprietary Kinect-specific skeletal model to obtain human motion data. However, for certain applications, the Kinectspecific skeletal model may not be adequate for some rigorous ergonomics assessments because it lacks clear anatomical definitions for some joints [5,15] and has insufficient anatomical landmarks [12]. In addition, as this technology evolves quickly, analyses directly derived from the Kinect-specific skeletal model may eventually be superseded [6].…”
Section: Introductionmentioning
confidence: 99%